Analisis Yuridis Tanggung Jawab Hukum Atas Kebijakan Penerapan KRIS Di Wilayah NTT - Wulandari, Anggi Yudistia; Gorda, A.A.A Ngr. Sri Rahayu (Unram Law Review, 2024)
Data on the availability of beds, especially for class three in healthcare facilities, particularly in NTT, shows the unpreparedness of hospitals to implement KRIS until June 30, 2025. Various controversies that may arise after the implementation of KRIS, especially if Healthcare Facilities are unable to meet KRIS standards by June 30, 2025. This research aims to analyze the implementation of KRIS provisions and the legal consequences for hospitals collaborating with BPJS Kesehatan. This research is normative in nature. The enactment of Presidential Regulation No. 59 of 2024 regarding KRIS. The policy related to the implementation of KRIS has not yet provided protection and legal certainty for the parties involved, including the payment system, so the Ministry of Health must review the rules and sanctions that will be imposed if healthcare providers are unable to meet the criteria outlined in the Presidential Regulation. There has not yet been a more in-depth explanation regarding the sanctions and legal consequences that will arise if, by June 30, 2025, healthcare facilities are unable to meet KRIS standards. The government must provide an explanation of the legal consequences if healthcare facilities are unable to meet the criteria outlined in the Presidential Regulation. BPJS Kesehatan must also prepare the derivative regulations from the Presidential Decree and review the Cooperation Agreement with hospitals to minimize the risk of legal consequences in the implementation of KRIS.